2011
DOI: 10.1039/c1fd00035g
|View full text |Cite
|
Sign up to set email alerts
|

The influence of the optical pulse shape on excited state dynamics in provitamin D3

Abstract: Broadband visible transient absorption spectroscopy was used to characterize the excited state population of 7-dehydrocholesterol (provitamin D3, DHC) following excitation by UV pulses with systematically varied linear chirp. These experiments demonstrate that the phase of the excitation pulse can modify the observed excited state decay. The results suggest that coherent mechanisms involving multiple interfering pathways may be exploited to control branching between excited state pathways and manipulate produc… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
24
0

Year Published

2012
2012
2017
2017

Publication Types

Select...
6

Relationship

3
3

Authors

Journals

citations
Cited by 9 publications
(26 citation statements)
references
References 37 publications
2
24
0
Order By: Relevance
“…The biexponential nature of the ESA decay can be explained within the context of two different models -sequential internal conversion between two distinct excited states, or rapid branching along two distinct pathways followed by parallel decay of these two populations. The parallel model seems more consistent with the experimental data, 5,99 and is supported by a recent computational study on Pro. 6,37 Furche and coworkers performed NAMD simulations of Pro along with the CHD simulations discussed above.…”
Section: Excited State Properties Of Provitamin Dsupporting
confidence: 81%
“…The biexponential nature of the ESA decay can be explained within the context of two different models -sequential internal conversion between two distinct excited states, or rapid branching along two distinct pathways followed by parallel decay of these two populations. The parallel model seems more consistent with the experimental data, 5,99 and is supported by a recent computational study on Pro. 6,37 Furche and coworkers performed NAMD simulations of Pro along with the CHD simulations discussed above.…”
Section: Excited State Properties Of Provitamin Dsupporting
confidence: 81%
“…This previtamin D 3 triene structure then undergoes a [1,7] sigmatropic hydride shift to form cholecalciferol (vitamin D 3 ) . In contrast to the ring-opening photoreaction, which occurs on a time scale of picoseconds, the thermal hydride shift occurs on the order of hours to days. The photochemistry of vitamin D has received much experimental , , and theoretical , attention due to the fundamental biological importance of the reaction and even its potential use in photoactivated devices …”
Section: Introductionmentioning
confidence: 99%
“…In particular, Sension and co-workers have conducted rigorous studies on CHD and a number of its derivatives in solution (e.g., alphaphellandrene, a-TP) [126,128,134,135]. This group has also shown that the basic physics translates to larger systems with cyclic diene moieties such as provitamin D [135][136][137]. Fig.…”
Section: Probing Ultrafast Excited State Dynamics In Ring Opening Sysmentioning
confidence: 95%